Waterbird Communities in Subsidence Wetlands Created by Underground Coal Mining in China: Effects of Multi-Scale Environmental and Anthropogenic Variables. (14th September 2018) - Li, Chunlin; Yang, Sen; Zha, Daode; Zhang, Yong; de Boer, Willem F.
Summary: Underground coal mining in the North China Plain has created large-scale subsidence wetlands that may attract waterbirds that use them as complementary habitats. However, no study has been conducted to understand avian use of these created wetlands, inhibiting the formulation of effective management plans. Here, we carried out 12 semi-monthly surveys in 55 subsidence wetlands during the 2016–2017 migration and wintering period and performed direct multivariate analyses, combined with variance partitioning, to test the effects of multi-scale habitat variables on the waterbird assemblages. A total of 89 349 waterbirds representing 60 species were recorded, with seasonal fluctuations in species richness and bird abundance. Waterbird community structures were shaped by four groups of variables at local, landscape and human levels with different effects among seasons. Anthropogenic disturbance was the most important factor group, negatively affecting most guilds. Waterbirds in this human-dominated environment are under a variety of potential threats that should be further studied. The subsidence wetlands are still expanding, and if managed effectively, may provide important complementary habitats for a wide array of waterbird species, particularly for those migrating along the East Asian–Australasian Flyway. Our study provides key baseline data regarding the waterbird communities and may help with the designing of effective management and conservation plans.